Rhabdomyolysis Associated With Heated Massage Therapy in a Patient Without Major Trauma: A Case Report - Ashani Ratnayake; Sayomi Warnakula; Yasitha Handapangoda; Udara Rathnayake; Lasanthika Athapaththu; Sanduni Rupasinghe (Clinical Case Reports, 2026)
ABSTRACT A 29‐year‐old professional dancer developed rhabdomyolysis after distal radial fracture fixation complicated by laryngospasm, negative pressure pulmonary oedema, suxamethonium use, and ICU admission. Creatine phosphokinase (CPK) peaked at 36,429 U/L with dark urine and hyperkalaemia. Recent prolonged heated massage‐bed use, with minor trauma and suxamethonium, may have contributed. Biopsy confirmed skeletal muscle necrosis.